Using scalable vector graphics to evolve art. (2016) - Heijer, Eelco Den; Eiben, A.E.
In this paper, we describe our investigations of the use of scalable vector graphics as a genotype representation in evolutionary art. We describe the technical aspects of using SVG in evolutionary art, and explain our custom, SVG specific operators initialisation, mutation and crossover. We perform two series of experiments; in the first series of experiments, we investigate the feasibility of SVG as a genotype representation for evolutionary art, and evolve abstract images using a number of aesthetic measures as fitness functions. In the second series of experiments, we used existing images as source material. We also designed and implemented an ad-hoc aesthetic measure for 'pop-art' and used this to evolve images that are visually similar to pop-art. All experiments described in this paper are done without a human in the loop. All images and SVG code examples in this paper are available at http://www.eelcodenheijer.nl/research.